Spatiotemporal Distribution of Phytoplankton Functional Groups in Baihua Reservoir: Implications for Ecosystem Management - Zhongxiu Yuan; Yan Chen; Si Zhou; Yugui Peng; Jing Xiao; Qiuhua Li (Biology)
Functional groups are an effective method for assessing water quality. From January 2020 to December 2023, the phytoplankton and environmental variables at five sites in Baihua Reservoir (BHR) were collected once a month. The succession rate (SR) and the average variation degree (AVD) of the functional groups were determined, and the corresponding driving factors were analyzed by using the Random Forest model, hierarchical partitioning, and Mantel test. A total of 95 phytoplankton species belonging to 7 taxonomic categories were identified, which can be divided into 27 functional groups and 8 dominant functional groups (B, D, L0, P, S1, W1, W2, Y). B, L0, and Y occupied dominant positions in spatiotemporal succession, indicating that the water body was in a mesotrophic to eutrophication state. Water temperature, total nitrogen, and transparency were the key factors driving the functional groups’ succession. Total nitrogen, total phosphorus, permanganate index, and dissolved oxygen were significantly positively correlated with AVD (n = 230; p < 0.01). SR not only directly positively affected AVD (n = 230; p < 0.05) but also indirectly affected AVD by affecting physicochemical factors. Understanding the relationship between the succession, stability, and environmental factors of functional groups is of great significance for algae management and the prevention of water bloom.